2016
DOI: 10.1007/s00345-016-1987-z
|View full text |Cite
|
Sign up to set email alerts
|

The new grasper-integrated single use flexible cystoscope for double J stent removal: evaluation of image quality, flow and flexibility

Abstract: In terms of quality of vision and water flow, the FC Isiris α is comparable to the other digital FC tested. Field of view is narrower. The results displayed a valid alternative to the standard procedure for DJ removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 5 publications
1
32
0
Order By: Relevance
“…The authors also indicated that the deflection angle of Isiris™ increased when the grasper was outside the device. They concluded that Isiris™ was comparable to other cystoscopes in terms of quality of vision and water flow (5).…”
Section: Discussionmentioning
confidence: 85%
“…The authors also indicated that the deflection angle of Isiris™ increased when the grasper was outside the device. They concluded that Isiris™ was comparable to other cystoscopes in terms of quality of vision and water flow (5).…”
Section: Discussionmentioning
confidence: 85%
“…Olympus ® CYF5, Olympus ® CYF-VH, Storz ® 11272C1, and Vision Science ® CST 5000 EndoSheath in the laboratories. 50 In their study, they found that Isiris α's vision and water flow are comparable to other digital flexible cystoscopes although the field of view is noted to be narrower on Isiris α™. Nevertheless, Talso et al have concluded that Isiris α™ is a viable and good alternative tool to remove ureteric stents.…”
Section: Isiris α™mentioning
confidence: 90%
“…A single case of grasper failure has been reported in which the manufacturing company provided a replacement cystoscope [ 14 ]. The image quality of the Isiris system has been deemed to be comparable to other flexible cystoscopes and although there was a narrower field of view, this was adequate for the purpose of stent removal [ 15 ]. In our study, no case of Isiris failure was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also consider the environmental impact of using disposable scopes. It is plausible that Isiris scopes can be developed further to overcome the field of view, which could allow diagnostic procedures to be carried out using the second generation of these scopes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%